Can Quality Assurance Beat Corruption in Higher Education? - Glendinning, Irene (International Higher Education, 2022)
Corruption undermines the operational basis for civil and cultural society. Corruption in higher education or research leads to an erosion of trust in academic credentials and claims of scientific breakthroughs. External bodies tasked with quality assurance and accreditation of higher education providers have an important role for ensuring that appropriate standards are maintained. However, in recent research, responses from reputable bodies to concerns about corruption did not always provide the expected reassurances.